2017
DOI: 10.1103/physrevb.96.134502
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoresistance in the superconducting state at the (111) LaAlO3/SrTiO3 interface

Abstract: Condensed matter systems that simultaneously exhibit superconductivity and ferromagnetism are rare due the antagonistic relationship between conventional spin-singlet superconductivity and ferromagnetic order. In materials in which superconductivity and magnetic order is known to coexist (such as some heavy-fermion materials), the superconductivity is thought to be of an unconventional nature. Recently, the conducting gas that lives at the interface between the perovskite band insulators LaAlO3 (LAO) and SrTiO… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…[14][15][16] Electric transport measurements have shown that the (111) LAO/STO interface exhibits many of the properties already seen in (001) LAO/STO, including a coexistence of superconductivity and magnetism. [17][18][19][20] However, the feature that distinguishes the (111) interface from the (001) interface is the strong anisotropy with respect to surface crystal direc-arXiv:1708.04809v2 [cond-mat.str-el] 28 Aug 2017 tion seen in almost all properties, including conductivity, Hall effect, superconductivity, quantum capacitance and longitudinal magnetoresistance. [17][18][19] By measuring the temperature dependence of the resistance and Hall coefficient, we show here that this anisotropy may be a signature of an electronic nematic transition that onsets at low temperatures, far from any known structural transitions of the system.…”
mentioning
confidence: 99%
“…[14][15][16] Electric transport measurements have shown that the (111) LAO/STO interface exhibits many of the properties already seen in (001) LAO/STO, including a coexistence of superconductivity and magnetism. [17][18][19][20] However, the feature that distinguishes the (111) interface from the (001) interface is the strong anisotropy with respect to surface crystal direc-arXiv:1708.04809v2 [cond-mat.str-el] 28 Aug 2017 tion seen in almost all properties, including conductivity, Hall effect, superconductivity, quantum capacitance and longitudinal magnetoresistance. [17][18][19] By measuring the temperature dependence of the resistance and Hall coefficient, we show here that this anisotropy may be a signature of an electronic nematic transition that onsets at low temperatures, far from any known structural transitions of the system.…”
mentioning
confidence: 99%
“…21,22 How this complex band structure affects various properties is just beginning to be explored. 23,24 Recent transport experiments on (111) LaAlO 3 /STO (LAO/STO) have shown surprising anisotropies related to the crystalline axes, dependent on an applied V g , 9,[25][26][27][28][29] as well as a non-monotonic dependence of phase coherence time τ φ and spin-orbit scattering time τ so on V g . 30 Here we report studies of the MR of LSAT deposited epitaxially on (111) STO.…”
mentioning
confidence: 99%
“…11 Additionally, as we have expolored in our earlier work the nonlinear differential resistance in the Ar/H 2 annealed samples is weakly anisotropic, especially near I c . 24 However, the most striking feature of these data is that the currentvoltage characteristics also depend on the gate voltage V F at which the samples were cooled, even when V g is subsequently repeatedly changed over the same range. The difference is persistent: as noted in Section II, data were taken after the gate voltage had been swept repeatedly between +/-100 V at 30 mK; the sample remembers the voltage V F at which it was cooled.…”
Section: Resultsmentioning
confidence: 99%
“…9,[21][22][23] While other groups have reported observing superconductivity in (111) oriented LAO/STO interfaces, the two new effects we report here point to the potentially exotic nature of the superconducting correlations in this system. 24,25…”
Section: Introductionmentioning
confidence: 99%